Wine Microbial Consortium: Seasonal Sources and Vectors Linking Vineyard and Winery Environments - Camilo, Sofia (2022)
ABSTRACT: Winemaking involves a wide diversity of microorganisms with different roles in the process. The wine microbial consortium (WMC) includes yeasts, lactic acid bacteria and acetic acid bacteria with different implications regarding wine quality. Despite this technological importance, their origin, prevalence, and routes of dissemination from the environment into the winery have not yet been fully unraveled. Therefore, this study aimed to evaluate the WMC diversity and incidence associated with vineyard environments to understand how wine microorganisms overwinter and enter the winery during harvest. Soils, tree and vine barks, insects, vine leaves, grapes, grape musts, and winery equipment were sampled along four seasons. The isolation protocol included: (a) culture-dependent microbial recovery; (b) phenotypical screening to select fermenting yeasts, lactic acid, and acetic acid bacteria; and (c) molecular identification. The results showed that during all seasons, only 11.4% of the 1424 isolates presumably belonged to the WMC. The increase in WMC recovery along the year was mostly due to an increase in the number of sampled sources. Acetic acid bacteria (Acetobacter spp., Gluconobacter spp., Gluconoacetobacter spp.) were mostly recovered from soils during winter while spoilage lactic acid bacteria (Leuconostoc mesenteroides and Lactobacillus kunkeii) were only recovered from insects during veraison and harvest. The fermenting yeast Saccharomyces cerevisiae was only isolated from fermented juice and winery equipment. The spoilage yeast Zygosaccharomyces bailii was only recovered from fermented juice. The single species bridging both vineyard and winery environments was the yeast Hanseniaspora uvarum, isolated from insects, rot grapes and grape juice during harvest. Therefore, this species appears to be the best surrogate to study the dissemination of the WMC from vineyard into the winery. Moreover, the obtained results do not evidence the hypothesis of a perennial terroir-dependent WMC given the scarcity of their constituents in the vineyard environment along the year and the importance of insect dissemination.